Current state of evidence-based practice in clinical physiotherapy - Ronel Roos (South African Journal of Physiotherapy)
Evidence-based practice (EBP) is a process that a clinician undertakes, implementing his or her clinical expertise while collaborating with the patient or client in the sociocultural context of care using the best available research evidence to inform practice. The approach has evolved over time in relation to its name, definition, scope and specific steps. In October 2001, member organisations of World Physiotherapy (then the World Confederation for Physical Therapy) gathered in London to discuss the status of EBP in the profession and to gain buy-in from regions to ensure that EBP would become a culture of practice in all regions. The purpose of this article is to describe the current state of EBP during physiotherapy as presented in the literature. Two decades have passed since this meeting, with noteworthy developments in clinical practice, education and research synthesis. Physiotherapists’ opinions and attitudes towards EBP are favourable but do not always ensure good implementation and execution during clinical practice. Standardised outcome measures to evaluate the EBP of physiotherapists are available. Barriers remain, which are multifactorial, and facilitators such as time, support and education are integral to optimise implementation. The launch of the Physiotherapy Evidence Database is one strategy that facilitates EBP in physiotherapy.